2014
DOI: 10.1016/j.scr.2014.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic elements and critical factors of cellular reprogramming revealed by stepwise global gene expression analyses

Abstract: A better understanding of the cellular and molecular mechanisms involved in the reprogramming of somatic cells is essential for further improvement of induced pluripotent stem (iPS) cell technology. In this study, we enriched for cells actively undergoing reprogramming at different time points by sorting the cells stained with a stem cell-selective fluorescent chemical probe CDy1 for their global gene expression analysis. Day-to-day comparison of differentially expressed genes showed highly dynamic and transie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 44 publications
1
29
0
Order By: Relevance
“…The ability to genetically reprogram a somatic cell to an induced pluripotent stem cell (iPSC) represented a paradigm shift in stem cell research upon its first description ( Takahashi and Yamanaka, 2006 ) and provides great promise for regenerative medicine, but the process remains inefficient. It has been proposed that iPSC reprogramming is a stochastic process ( Hanna et al., 2009 ), but there is emerging evidence that it is deterministic with initiation, stabilization, and maturation stages ( Golipour et al., 2012 , Samavarchi-Tehrani et al., 2010 ) involving the coordinated temporal activation and repression of cell signaling pathways ( Park et al., 2014 , Polo et al., 2012 ). Reprogramming cells undergo profound changes in morphology, function, and metabolic activity with somatic cells that predominantly rely on mitochondrial respiration to produce ATP, switching to glycolysis ( Folmes et al., 2011 , Panopoulos et al., 2012 , Prigione et al., 2010 , Varum et al., 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…The ability to genetically reprogram a somatic cell to an induced pluripotent stem cell (iPSC) represented a paradigm shift in stem cell research upon its first description ( Takahashi and Yamanaka, 2006 ) and provides great promise for regenerative medicine, but the process remains inefficient. It has been proposed that iPSC reprogramming is a stochastic process ( Hanna et al., 2009 ), but there is emerging evidence that it is deterministic with initiation, stabilization, and maturation stages ( Golipour et al., 2012 , Samavarchi-Tehrani et al., 2010 ) involving the coordinated temporal activation and repression of cell signaling pathways ( Park et al., 2014 , Polo et al., 2012 ). Reprogramming cells undergo profound changes in morphology, function, and metabolic activity with somatic cells that predominantly rely on mitochondrial respiration to produce ATP, switching to glycolysis ( Folmes et al., 2011 , Panopoulos et al., 2012 , Prigione et al., 2010 , Varum et al., 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…The initiation phase is also characterised by a metabolic switch from oxidative phosphorylation to glycolysis [65] that occurs around 7 d after induction of reprogramming [66] and involves phosphatidylinositol-3-kinase (PI3K)/AKT signalling [53,67] . For example, Chen et al [67] have demonstrated that the PI3K/AKT pathway was activated during reprogramming in parallel with the upregulation of glycolytic gene expression, showing specifically that AKT activated 2 key glycolytic regulators, AS1060 and PFKB2.…”
mentioning
confidence: 99%
“…In recent years, optical molecular imaging has undergone substantial development into the direct visualisation of cellular features that are associated with disease processes. [1][2][3][4][5][6] In this context, the molecular complexity of the probes needed for optimal biological performance requires modern synthetic methods, oen beyond standard protocols. 7 Our group and others have demonstrated the value of peptide-based optical probes as powerful tools to monitor cellular events in real time.…”
Section: Introductionmentioning
confidence: 99%